Infantile segmental NF1 / Hypermelanic nevus. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2020)
Segmental peripheral neurofibromatosis type 1 (NF1) in children is characterized by the presence of café au lait spots distributed on only one body segment, while segmental NF1 in adults is characterized by the exclusive or prevalent presence of neurofibromas. Infantile segmental NF1 must be differentiated from hypermelanic nevus, which in the most extensive forms involves a cutaneous segment.